What's in a Word? Just vs. Fair vs. Appropriate Earnings for Self and Others - Jule Adriaans; Stefan Liebig; Clara Sabbagh; Guillermina Jasso (Social Justice Research, 2021)
Despite Rawls' famous call to distinguish between justice and fairness, these and other justice-related words often seem to be used interchangeably by both ordinary people and justice researchers. Based on a survey-embedded question wording experiment ( N 0.167em=0.167em4534) fielded in Germany as part of the GESIS Panel, we explore the effects of three justice words— "just," "fair," and "appropriate"—on the sense of justice about earnings for self and others. We observe differences in the just reward, justice evaluation, and justice consequences by justice word. For example, justice evaluations of one's own earnings are more negative, i.e., deeper in the underreward territory, signaling larger just rewards, when using "just" instead of "fair" or "appropriate" in the question wording. No such clear pattern emerges for justice evaluations of others' earnings. Our analyses show the decreasing effect of an underreward situation on psychosocial health to be significantly stronger in the "just" condition compared to the "fair" condition but do not reveal differential consequences by justice word for measures of satisfaction and trust. Overall, the observed differences by justice words are moderate in size. Nonetheless, our findings suggest caution for justice researchers in communicating with peers and respondents and warrant further inquiry extending research on the role of "justice language" to other language–country contexts.
Additional information: Open access funding enabled and organized by Projekt DEAL.
Keywords: 330; Justice words; Justice of earnings; Question wording; Survey-embedded experiment; German.Germany